Mutual trust between leader and subordinate and employee outcomes - Kim, Tae-Yeol; Wang, Jie; Chen, Junsong (Springer, 2016)
Stable and enduring cooperative relationships among people are primarily based on mutual trust. However, little evidence exists about the effects of mutual trust between supervisor and subordinate on work outcomes. To understand better the dynamics of trust in supervisor–subordinate relationships, we examined how mutual trust between supervisor and subordinate is associated with work outcomes. Based on a sample of 247 subordinate–supervisor pairs, multilevel analyses revealed a positive effect of perceived mutual trust on task performance and interpersonal facilitation after controlling for trust in leader and felt trust. In addition, task performance and interpersonal facilitation increased as trust in leader and felt trust or trust in subordinate both increased.